PENERAPAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING BERBASIS MEDIA INTERAKTIF WORDWALL UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA - Salma, Alvis salma; Putri Pratani, Vista; Arif Syabani, Muhammad; Ekawati, Rooselyna; Mardiana, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This Classroom Action Research (PTK) aims to increase students' active learning in mathematics learning in class VII-B of SMP Negeri 6 Surabaya through the application of the Problem-Based Learning (PBL) learning model based on wordwall interactive media. This research was conducted in two cycles, with cycle I using the Problem-Based Learning learning model but not yet based on wordwall interactive media and cycle II using the Problem-Based Learning learning model already based on wordwall interactive media. The research subjects used were 32 students in class VII-B of SMP Negeri 6 Surabaya. Researchers use research objects in the form of students' level of activity and mathematics learning using Problem-Based Learning (PBL) based on wordwall interactive media. This research uses data collection techniques in the form of observation sheets and documentation. The results of the research showed that there was a significant increase in students' learning activity from cycle I to cycle II. In cycle I, the average percentage of students' active learning was 40.83% in the less active category. Meanwhile, in cycle II, the average percentage of students' active learning increased to 83.33% in the very active category. Based on the results and discussion, it can be concluded that the application of the Problem-BasedLearning learning model based on interactive wordwall media has been proven to increase students' active learning in mathematics learning in class VII-B SMP Negeri 6 Surabaya.